Comparison of crossed and parallel rod configurations used in posterior occipitocervical and atlantoaxial fixations: a retrospective cohort study - Mandi Cai; Haozhi Yang; Shuang Zhang; Chenfu Deng; Junlin Chen; Rencai Ma; Xiaobao Zou; Xiangyang Ma (Journal of Orthopaedic Surgery and Research)
Abstract Background This study is aimed to compare the differences in clinical outcomes between the crossed rod configuration and the parallel rod configuration applied in posterior occipitocervical and atlantoaxial fixations, and to assess the clinical applicability of crossed rods. Methods From January 2015 to December 2021, 21 patients with craniocervical junction disorders were treated surgically with the crossed rod technique (CR group). Meanwhile, 27 corresponding patients treated with the conventional parallel rod technique were included as control (PR group). Clinical data, internal fixation type, neurological status, clinical symptoms relief, image parameter, complications and bone fusion conditions were retrospectively analyzed and evaluated. Results No statistically significant differences were found in baseline characteristics, fixation type and postoperative complications between the two groups. Although the postoperative ADI was significantly reduced in both groups, the ADI was significantly greater in the CR group than that in the PR group after surgery and at the final follow-up (P < 0.05). All patients achieved bone fusion at 1-year postoperative follow-up except for one case in the PR group. However, patients in the CR group had a significantly higher fusion rate than those in the PR group at 3 months postoperatively (P < 0.05). Conclusions The application of a crossed rod configuration in posterior occipitocervical and atlantoaxial fixations provides good clinical applicability. Although this technique has a relatively weaker reduction force, it has greater fixation stability and a higher rate of early bone fusion. This technique could be an easy and viable alternative to the current parallel rod configuration for upper cervical surgery.